INFLUENCE LIFESTYLE, PRODUCT QUALITY AND PRICE PERCEPTIONS ON PURCHASE DECISIONS IN THE COMPANY JUNK FOOD IN LABUAN BAJO (KFC) - IBN Udayana; Agus Dwi Cahya; Natalia Dewi Fendal (Faculty of Economics and Business, Universitas Malikussaleh, 2022)
This study was conducted to examine the effect of lifestyle, product quality and price perception on Kentucky Fried Chicken in Labuan Bajo, either partially or simultaneously. The method used in this research is the explanatory method, with data collection techniques through questionnaires. The sampling technique used was purposive and proportional sampling. The sample is 105 people who are consumers who have bought/consumed KFC Labuan Bajo products. The analysis technique used is quantitative. Quantitative analysis using validity test, reliability test, classic assumption test, correlation coefficient, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test).The results of data analysis show that Lifestyle (X1) and Product Quality (X2) have a positive and significant effect on purchasing decisions, while Price Perception (X3) has no effect on purchasing decisions. Lifestyle (X1), quality of life (X2) and price perception (X3) have a significant simultaneous effect on Consumer Purchase Decisions (Y) for KFC products in Labuan Bajo. This shows that if Lifestyle, Product Quality and price perceptions are improved together, it will increase Consumer Purchase Decisions.